Hi . here’s your answer. Step by step solution : STEP 1 : Equation at the end of step 1 ((x3) – 2×2) – 4x = 0 STEP 2 : STEP 3 : Pulling out like terms 3.1 Pull out like factors : x3 – 2×2 – 4x = x • (x2 – 2x – 4) Trying to factor by splitting the middle term 3.2 Factoring x2 – 2x – 4 The first term is, x2 its coefficient is 1 . The middle term is, -2x its coefficient is -2 . The last term, “the constant”, is -4 Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4 Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -2 . -4 + 1 = -3 -2 + 2 = 0 -1 + 4 = 3 Observation : No two such factors can be found !! Conclusion : Trinomial can not be factored. Hope it helped you. please mark this answer as brainiest. Reply
Hi .
here’s your answer.
Step by step solution :
STEP
1
:
Equation at the end of step 1
((x3) – 2×2) – 4x = 0
STEP
2
:
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
x3 – 2×2 – 4x = x • (x2 – 2x – 4)
Trying to factor by splitting the middle term
3.2 Factoring x2 – 2x – 4
The first term is, x2 its coefficient is 1 .
The middle term is, -2x its coefficient is -2 .
The last term, “the constant”, is -4
Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4
Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -2 .
-4 + 1 = -3
-2 + 2 = 0
-1 + 4 = 3
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored.
Hope it helped you.
please mark this answer as brainiest.